The sharp Sobolev inequality in quantitative form - Cianchi, Andrea; Fusco, Nicola; Maggi, Francesco; Pratelli, Aldo (Journal of the European Mathematical Society, 2009)
A quantitative version of the sharp Sobolev inequality in W (ℝ), 1 < p < n, is established with a remainder term involving the distance from the family of extremals. © European Mathematical Society 2009.